(untitled) (AYUSHDHARA, 2024)
Seborrheic Keratosis (SK), commonly known as seborrheic warts or basal cell papilloma, is a prevalent benign skin tumor that is often removed for cosmetic reasons due to its appearance. These lesions can manifest in various forms and locations on the body, making them a common concern for many individuals seeking dermatological care. Within the Siddha system of medicine, such skin growths are classified as “Marul.” This case report discusses the successful treatment of a 30-year-old male patient diagnosed with SK on the scalp. The patient underwent a comprehensive four-day regimen of Kallani Kalimbu, a Siddha-based topical preparation rich in natural ingredients. Remarkably, this treatment resulted in the complete resolution of the lesion, with no visible scarring and no recurrence noted during follow-up visits over the course of several months. This case underscores the potential effectiveness of Kallani Kalimbu as a minimally invasive and cost-effective therapeutic option for managing SK. While these findings are promising, further studies involving larger controlled trials are essential to validate the efficacy and safety of Kallani Kalimbu for SK and similar skin conditions. Expanding the evidence base through rigorous research could facilitate the integration of traditional Siddha practices into contemporary dermatological treatment protocols, thereby enhancing the overall management of benign skin lesions and improving patient outcomes.